России первая любовь: Мой Пушкин: Стихотворения, поэмы, проза / Николай Доризо - Доризо Николай Константинович (Современник, 1986)
Экземпляры: (20190918) / Инвентарный номер: / Сис.шифр: Р2 / Авт.знак: Д68 / ББК: Р2